IMPLEMENTASI PERATURAN MENTERI KESEHATAN REPUBLIK INDONESIA NOMOR 2052/MENKES/PER/X/2011 TENTANG PELAKSANAAN IZIN PRAKTIK DOKTER DAN UPAYA PENEGAKANNYA DI KOTA YOGYAKARTA - , HARIS ARDHI PRADIPTA; , Dwi Haryati, S.H., M.H ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Health is one of the common elements that should be realized in accordance with the purpose of establishing the State of Indonesia, as stated in the Preamble of the 1945 Constitution. One of embodiment of health care services to the community, among others, with the practices of physicians who are in the middle of society. This thesis discusses the general implementation of the Regulation of the Minister of Health of the Republic of Indonesia Number 2052/MENKES/PER/X/2011 by the competent authority, in this case is Health Department of Yogyakarta City. Type of research conducted in the writing of this law is that empirical legal research study based on the legal norms applicable law and supported by field data that describes the reality of the matter. The study was conducted by interviewing the relevant parties, in this case is Health Department of Yogyakarta City and the doctors' who has a workplace in the city of Yogyakarta. Based on the results, it can be concluded that the Healt Department of Yogyakarta City in implementing Regulation of the Minister of Health of the Republic of Indonesia Number 2052/MENKES/PER/X/2011 still not maximal. Especially in terms of monitoring and dissemination of these regulations to the practicing physician in the city of Yogyakarta. The result is expected to be useful for people, especially people receiving medical services, to find out how the implementation should be done by the government, especially in the field of medical practice.